factorise by splitting the middle term 2x ^2-5/6x+1/12
Answers
Answered by
2
Step-by-step explanation:
Factorise by splitting the middle term
Given Quadratic expression :
2x²-5x/6+1/12
Find L.C.M of 6 and 12 , we get
LCM = 12
= (24x²-10x+1)/12
Splitting the middle term, we get
= (1/12)[24x²-6x-4x+1]
=(1/12)[6x(4x-1)-1(4x-1)]
= (1/12)[(4x-1)(6x-1)]
Therefore,
2x²-5x/6+1/12 = (1/12)(4x-1)(6x-1)
Hope it's help you pleaseeeee mark me as brainliest pleaseeeee
Answered by
0
Step-by-step explanation:
SOLUTION IS ATTACHED...
Hope it helps...
please mark brainliest...
Attachments:
![](https://hi-static.z-dn.net/files/df0/472f2cf28cce30ec628713da095ad82d.jpg)
Similar questions